RECLAIMING URBAN SPACE: A STUDY OF COMMUNITY GARDENS IN POZNAŃ - Maćkiewicz, Barbara; Puente Asuero, Raúl; Pawlak, Krystyna (Quaestiones Geographicae, 2018)
In this paper, we discuss the presence of community gardens in urban spaces and the types of activities performed there, using the city of Poznań as a case study. First, based on interviews with representatives of selected non-governmental organisations, analyses of available Internet sources as well as our own field research, cartographic and photographic documentation, we identify community gardens in the space of the city and explore their formation process. In the course of our study we also concentrate on the type of garden location. In addition, we devote our attention to the gardens which have disappeared from the fabric of the city. Our study reveals that community gardens currently operating in Poznań are established in non-central locations. These gardens are scattered in various parts of the city. Only in the Łazarz district there are two community gardens. Most frequently, community gardens are established on plots between old blocks of flats and tenement houses. Two gardens are located on underdeveloped greenery near the Warta River and in two city parks. A detailed examination of the events held in the community gardens in the Łazarz district in the years 2014–2017 shows that they had a very diversified character. Both of them turned out to be multifunctional, i.e. hosted meetings devoted to agriculture and horticulture, environmental education, artistic events, DIY and recreation. However, the percentage of events in the structure of the meetings organised in the gardens differed considerably.